The miR‐139‐5p regulates proliferation of supratentorial paediatric low‐grade gliomas by targeting the PI3K/AKT/mTORC1 signalling. (25th March 2018) - Catanzaro, G.; Besharat, Z. M.; Miele, E.; Chiacchiarini, M.; Po, A.; Carai, A.; Marras, C. E.; Antonelli, M.; Badiali, M.; Raso, A.; Mascelli, S.; Schrimpf, D.; et al.
Abstract : Aims: Paediatric low‐grade gliomas (pLGGs) are a heterogeneous group of brain tumours associated with a high overall survival: however, they are prone to recur and supratentorial lesions are difficult to resect, being associated with high percentage of disease recurrence. Our aim was to shed light on the biology of pLGGs. Methods: We performed microRNA profiling on 45 fresh‐frozen grade I tumour samples of various histological classes, resected from patients aged ≤16 years. We identified 93 microRNAs specifically dysregulated in tumours as compared to non‐neoplastic brain tissue. Pathway analysis of the microRNAs signature revealed PI3K/AKT signalling as one of the centrally enriched oncogenic signalling. To date, activation of the PI3K/AKT pathway in pLGGs has been reported, although activation mechanisms have not been fully investigated yet. Results: One of the most markedly down‐regulated microRNAs in our supratentorial pLGGs cohort was miR‐139‐5p, whose targets include the gene encoding the PI3K's (phosphatidylinositol 3‐kinase) catalytic unit, PIK3CA . We investigated the role of miR‐139‐5p in regulating PI3K/AKT signalling by the use of human cell cultures derived from supratentorial pLGGs. MiR‐139‐5p overexpression inhibited pLGG cell proliferation and decreased the phosphorylation of PI3K target AKT and phosphorylated‐p70 S6 kinase (p‐p70 S6K), a hallmark of PI3K/AKT/mTORC1 signalling activation. The effect of miR‐139‐5p was mediated by PI3K inhibition, as suggested by the decrease in proliferation and phosphorylation of AKT and p70 S6K after treatment with the direct PI3K inhibitor LY294002. Conclusions: These findings provide the first evidence that down‐regulation of miR‐139‐5p in supratentorial pLGG drives cell proliferation by derepressing PI3K/AKT signalling.